Evaluation of the conditions of accessibility and inclusion of the Ifsul library - câmpus Sapucaia do Sul: accessible library project (Revista Brasileira de Iniciação Científica, 2023)
This paper aims to evaluate the conditions of accessibility and inclusion of the library of the Instituto Federal Sul-rio-grandense - Sapucaia do Sul câmpus to serve people with disabilities. This is a section of the undergraduate research project "Accessible Library". It was carried out an exploratory research of descriptive nature, and mixed approach, through literature review and field research. Data were collected using the instrument for the evaluation of accessibility conditions in libraries made available by the Brazilian Federation of Library Associations (2018). The conclusions are directed towards the improvement in library accessibility.
Keywords: Accessibility; Inclusion; Libraries